In the intimacy of the darkness: Genetic polyandry in deep‐sea luminescent lanternsharks Etmopterus spinax and Etmopterus molleri (Squaliformes, Etmopteridae). Issue 6 (20th April 2020) - Duchatelet, Laurent; Oury, Nicolas; Mallefet, Jérôme; Magalon, Hélène
Abstract: Multiple paternity seems common within elasmobranchs. Focusing on two deep‐sea shark species, the velvet belly lanternshark ( Etmopterus spinax ) and the slendertail lanternshark ( Etmopterus molleri ) we inferred the paternity in 31 E. spinax litters from Norway (three to 18 embryos per litter) and six E. molleri litters from Japan (three to six embryos), using 21 and 10 specific microsatellites, respectively. At least two E. spinax litters were sired from multiple fathers each, with highly variable paternal skew (1:1 to 9:1). Conversely, no clear signal of genetic polyandry was found in E. molleri .